Zakat for Digital Literacy: Closing the Orphaned-Urban Tech-Gap to Prevent Future Unemployment Crises - Wahyudi, Ickhsanto; Rahmawati, Rahmawati; Amelia, Erika; Yama, Indo (International Journal of Zakat, 2026)
Purpose This paper proposes a zakat-funded digital literacy voucher as a policy instrument to support Indonesia’s national digital talent and youth employment agenda by expanding access to market-relevant skills for unemployed and out-of-school urban youth. Design/Methodology/Approach The study adopts a policy-oriented conceptual approach that integrates labor market evidence, digital skills demand analysis, and zakat governance. It designs a Sharīʿah-compliant, restricted-purpose voucher mechanism administered by zakat institutions and redeemable at accredited digital training providers, aligned with outcome-based financing principles. Findings The proposed model demonstrates that zakat can be operationalized as an active labor market policy complementing existing government programs such as digital talent development initiatives. The voucher system improves targeting, transparency, and accountability by linking disbursement to training completion and certification outcomes. It also addresses affordability constraints that limit participation of vulnerable urban youth in private digital training programs. Research limitations/implicationsThis study is limited to policy design and does not assess implementation outcomes. Future research should evaluate pilot programs in selected urban areas to measure employment impacts, fiscal efficiency, and inter-institutional coordination. Practical implicationsThe model provides a framework for zakat institutions and policymakers to integrate Islamic social finance with national digital talent programs. Social implicationsThe program supports youth employment, reduces NEET risk, and strengthens economic inclusion in the digital economy. Originality/value The paper offers a practical policy framework for integrating zakat into Indonesia’s digital workforce ecosystem, positioning Islamic social finance as a complementary instrument to public employment and digital inclusion strategies.